A multi-dimensional analysis of person-centred collaborative practice for designing an educational curriculum in continuing care centres. Issue 1 (January 2015) - Coulson, Irene Katherina; Galenza, Shirley; Bratt, Sharon; Foisy-Doll, Colette R.; Haase, Mary
Abstract A significant transformation occurring in the continuing care industry is an attempt to shift the culture from impersonal institutions into true person-centred care (PCC) homes. This approach re-orients the facility's values, attitudes, norms and hierarchies while creating flexible role descriptions to promote collaborative teamwork. PCC practices will require healthcare teams to develop new approaches that empower residents and families to become partners in the development of a plan of care. This report outlines a study, which will gather data from an organizational policy analysis and interviews with residents and healthcare staff. These data will be examined through a sociological lens to identify areas for team improvement. The results will guide the design of a training curriculum to be delivered using traditional and multi-modal hi-fidelity simulation methods.